Division of Magnetic Flux Rope via Magnetic Reconnection Observed in the Magnetotail - Xinmin Li; Rongsheng Wang; Quanming Lu (Geophysical Research Letters, 2023)
Abstract Using high‐resolution data from Magnetospheric Multiscale (MMS) mission, we report an intense current layer at the center of a flux rope (FR) in the magnetotail. The intense current layer is caused by the compression of the ion bulk flows at the center of a FR rather than two interlaced flux tubes reported at the magnetopause previously. The intense current layer has been identified as an electron diffusion region of the magnetic reconnection, and the hall magnetic field generated by magnetic reconnection makes the FR show crater‐shaped. The reconnecting current layer is supported by the poloidal magnetic field of the FR, and it is dividing the FR into two secondary FRs. The observations suggest that magnetic FR can be compressed easily to excite instability inside it as it is propagating in the magnetotail current sheet, thus changing its magnetic topology.